Geographic, social, and behavioural factors associated with leptospirosis cases reported to the National Public Health Surveillance System in Antioquia, Colombia, 2010-2021 - Loaiza-Echeverri, Erica (2025)
The aim of this study was to describe and characterize the human population in terms of sociodemographic and behavioural characteristics. In addition, the associated factors of leptospirosis cases in Antioquia reported to the National Public Health Surveillance System between 2010 and 2021 were explored, stratifying municipalities according to the incidence of cases of this disease. A cross-sectional, quantitative, observational study with an analytical approach was conducted. A total of 2034 records of patients who consulted health centres in various regions of the department of Antioquia for clinical manifestations characteristic of leptospirosis were analysed. The highest incidence rates were recorded in the municipalities of Vigía del Fuerte (1.79/1000 inhabitants), followed by the municipality of Turbo (1.76/1000 inhabitants), and the municipality of Apartadó (1.41/1000 inhabitants). The variables that were considered as factors associated with leptospirosis positivity were contact with animals (p=0.025, RP=1.94), contact with rats (p=0.040, RP=1.92), contact with stagnant water (p=0.044, RP=1.96) and contact with water (p=0.048, RP=1.91).